Applying Six Sigma to Assess Quality Culture in a Senior High School: A Strategic Management Perspective - Dewanto, Heru; Setiawati, Deni (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study examines the application of Six Sigma to assess quality culture in a senior high school in Bandung, with potential relevance for broader educational settings. Method: Employing a mixed-method case study design, the research combined interviews and Focus Group Discussions (FGDs) to identify the main dimensions of quality culture, followed by a questionnaire-based assessment involving 42 teacher respondents. Unlike conventional school quality assessments, which primarily rely on descriptive and qualitative evaluations, this study integrates the DMAIC (Define, Measure, Analyze, Improve, and Control) framework with quantitative Six Sigma metrics to establish objective benchmarks for assessing school quality culture. School performance was evaluated across eight indicators using Defects Per Million (DPM) and sigma levels. Results: The analysis revealed baseline sigma levels ranging from 2.14σ to 3.90σ. The lowest-performing dimensions were stakeholder involvement in developing the vision and mission 2.14σ, understanding of the vision and mission 2.25σ, and school programs that reflect social values 2.59σ, indicating that these dimensions require substantial improvement to strengthen the school's quality culture. Novelty: This study demonstrates that Six Sigma provides a practical evaluative framework by establishing baseline sigma levels as objective benchmarks for assessing school quality culture, prioritizing improvement initiatives, and supporting strategic management and continuous quality improvement in educational institutions.